2019
DOI: 10.2147/ceor.s222879
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cost-Effectiveness Of Midostaurin In The Treatment Of Acute Myeloid Leukemia With The FLT3 Mutation In Spain</p>

Abstract: The addition of midostaurin to standard chemotherapy (cytarabine and daunorubicin) has shown significant improvements in the survival of patients with acute myeloid leukemia with the FLT3 mutation (FLT3-AML). The objective of this study was to determine whether this intervention would be cost-effective in Spain. Methods: A partitioned survival model with five health states was developed (diagnosis and induction, complete remission, no complete remission, transplantation and death). A lifetime time horizon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Arenaza et al, in a pharmacoeconomic multicenter Spanish study in de novo FLT3 positive AML patients from the RATIFY study, showed an overall cost of EUR 121,374 in non-alloHSCT patients and EUR 159,900 (no midostaurin arm) in alloHSCT patients. These higher reimbursements could be explained by the fact that in these cohorts patients were younger and probably more fit and thus could receive more treatment schemes (with hospital admissions), including R/R episodes or alloHSCT [35]. Some limitations should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Arenaza et al, in a pharmacoeconomic multicenter Spanish study in de novo FLT3 positive AML patients from the RATIFY study, showed an overall cost of EUR 121,374 in non-alloHSCT patients and EUR 159,900 (no midostaurin arm) in alloHSCT patients. These higher reimbursements could be explained by the fact that in these cohorts patients were younger and probably more fit and thus could receive more treatment schemes (with hospital admissions), including R/R episodes or alloHSCT [35]. Some limitations should be addressed.…”
Section: Discussionmentioning
confidence: 99%